Endoplasmic reticulum stress-mediated cell death in liver injury - Zhang, Jian; Guo, Jiafu; Yang, Nannan; Huang, Yan; Hu, Tingting; Rao, Chaolong (Cell death & disease, 2022)
The endoplasmic reticulum is an important intracellular organelle that plays an important role in maintaining cellular homeostasis. Endoplasmic reticulum stress (ERS) and unfolded protein response (UPR) are induced when the body is exposed to adverse external stimuli. It has been established that ERS can induce different cell death modes, including autophagy, apoptosis, ferroptosis, and pyroptosis, through three major transmembrane receptors on the ER membrane, including inositol requirement enzyme 1α, protein kinase-like endoplasmic reticulum kinase and activating transcription factor 6. These different modes of cell death play an important role in the occurrence and development of various diseases, such as neurodegenerative diseases, inflammation, metabolic diseases, and liver injury. As the largest metabolic organ, the liver is rich in enzymes, carries out different functions such as metabolism and secretion, and is the body’s main site of protein synthesis. Accordingly, a well-developed endoplasmic reticulum system is present in hepatocytes to help the liver perform its physiological functions. Current evidence suggests that ERS is closely related to different stages of liver injury, and the death of hepatocytes caused by ERS may be key in liver injury. In addition, an increasing body of evidence suggests that modulating ERS has great potential for treating the liver injury. This article provided a comprehensive overview of the relationship between ERS and four types of cell death. Moreover, we discussed the mechanism of ERS and UPR in different liver injuries and their potential therapeutic strategies.